The Impact of the Number of Issuers and Transaction Value on the Growth of Islamic Invesment in the Indonesian Capital Market - Prawira, Adi; Nasfi, Nasfi (Denisya Smart Consulting, 2025)
This study aims to analyze the effect of the number of issuers and transaction value on investment growth in the Indonesian capital market. The research method used is multiple linear regression analysis with secondary data obtained from the annual report of the Indonesia Stock Exchange (IDX). The results showed that the number of issuers had a positive and significant effect on investment growth with a significant value of 0.00 which is smaller than alpha 0.05. Similarly, transaction value has a positive and significant effect on investment growth with a significant value of 0.00 which is smaller than alpha 0.05. Of the two independent variables, transaction value has a more dominant influence than the number of issuers. This finding is in line with capital market theory which states that liquidity and availability of investment instruments are important factors in encouraging investment growth. This research is expected to contribute to regulators, issuers, and investors in making strategic decisions to strengthen the development of the Indonesian capital market.